Beyond Leadership: How Transformational Leaders Foster Organizational Citizenship and Engagement through Psychological Empowerment - Mohammed Abdulrab; Kamal Ali Thabet Alwaleedi; Yaser Hasan Al-Mamary; Abdul Rahim Zumrah; Ali Nasser Ali Al-Tahitah; Al-Baraa Abdulrahman Al-Mekhlafi (Porcelain Publishing International Limited., 2025)
Index (Tier 2)